What over 100 drillings tell us: a new method for determining the Koenigsberger ratio of soils from magnetic mapping and susceptibility logging. Issue 4 (26th July 2020) - Pickartz, Natalie; Rabbel, Wolfgang; Rassmann, Knut; Müller‐Scheeßel, Nils; Furholt, Martin; Müller, Johannes; Cheben, Ivan; Wilken, Dennis; Wunderlich, Tina; Dreibrodt, Stefan
Abstract: We investigate the relative fractions of remanent and induced magnetization of the fillings of neolithic long pits in order to develop remanent magnetization as an additional parameter for the archaeological interpretation of magnetic maps. We determine the Koenigsberger ratio – the ratio between induced and remanent magnetization intensities – for key targets by combining magnetic mapping with downhole measurements of susceptibility, numerical modelling, and inversion computations. The susceptibility data were acquired in drill holes along profiles crossing the targets identified by magnetic mapping. The targets of this exemplary study are house‐accompanying pits at the Linearbandkeramik site Vráble 'Farské'. For this purpose, we conducted auger drillings with a point distance of 25 cm and measured the susceptibility with a downhole susceptometer. The resulting two‐dimensional susceptibility distributions were used to calculate synthetic magnetic anomalies corresponding to the case of solely induced magnetization. The comparison to the observed magnetic data showed a considerable discrepancy that can only be explained with remanent magnetization. To determine the Koenigsberger ratio we developed a new interpretation approach, using parts of the measured susceptibility distribution as a basis function. The free parameters of this numerical problem are determined by non‐linear inversion. We applied the novel approach to six exemplary profiles and found Koenigsberger ratios between 1.6 and 10.5 with the majority of the values being smaller than 4. These values apply to soil volumes with susceptibility values larger than 27–160 × 10 ‐5 SI. Laboratory measurements on soil samples were used to examine the possible causes of the observed magnetization. The analyses suggest that the increase in susceptibility and remanent magnetization in the pits is caused by an increase of the population of magnetotactic bacteria and deposition of magnetized material, followed by the alignment of the ferrimagnetic iron compounds in the waterlogged environment of the pits and accumulation of viscous remanent magnetization.